2017
DOI: 10.14249/eia.2017.26.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the environmental and ecological value indicators for railway development area selection

Abstract: :Recently mountain tourism has been promoted and introduction of railroads with utilizing mountain resources is being planned. With the government policies to increase the share of eco-friendly transportation on railroad, national double-tracking of single rail and improvement projects are on going. However, the eco-friendly railroad policy suggests the environmental impact assessment items only on air quality, water quality, geographical/geological features, fauna/flora,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The data were assembled considering factors presented in NatCap and preceding papers [19,36]. This study utilized data reported in previous studies in Korea for biomass input data [38,40,41]. To enhance the accuracy of the input data, this study applied the value of the forest growing stock per unit area by forest type multiplied by the carbon storage factor for the above-and below-ground biomass values [39].…”
Section: Invest Carbon Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The data were assembled considering factors presented in NatCap and preceding papers [19,36]. This study utilized data reported in previous studies in Korea for biomass input data [38,40,41]. To enhance the accuracy of the input data, this study applied the value of the forest growing stock per unit area by forest type multiplied by the carbon storage factor for the above-and below-ground biomass values [39].…”
Section: Invest Carbon Modelmentioning
confidence: 99%
“…The Habitat Quality model was designed to evaluate biod habitat quality index assigns values between 0.0 and 1.0, with higher values greater biodiversity. This mechanism can be explained using the following for four types of input data [40][41][42][43]. The first data point is the relative threat of source; the second is the maximum impact distance between habitats and sou threats (the impact of a source decreases with an increase in the distance).…”
Section: Invest Habitat Quality Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area was within 1 km of the Gyeong-ui Central Line [3,17]. Due to the linear form of the railway project, the raster-based point sampling method described by [17][18][19] was used. Valuable area for environmental quality conservation was the dependent variable in this study.…”
Section: Evaluation Of the Environmental Quality Valuementioning
confidence: 99%
“…Res. Public Health 2021, 18,11764 Author Contributions: D.Y.K. planned the study and contributed the main ideas; M.-K.K.…”
Section: Numerical Assessment Of Environmental Qualitymentioning
confidence: 99%